Circadian Clock Proteins in Mood Regulation - Partonen, Timo (Frontiers in Psychiatry, 2015)
Mood regulation is known to be affected by the change of seasons. Recent research findings have suggested that mood regulation may be influenced by the function of circadian clocks. In addition, the activity of brown adipocytes has been hypothesized to contribute to mood regulation. Here, the overarching link to mood disorders might be the circadian clock protein NR1D1 (nuclear receptor subfamily 1, group D, member 1).